TECHNOLOGIES FOR THE DEVELOPMENT OF THE LEXICAL-GRAMMATICAL ASPECTS OF THE SPEECH OF CHILDREN WITH SEVERE SPEECH DEFECTS (American Journal of Interdisciplinary Research and Development, 2024)
This article has studied and analyzed psychological, pedagogical and methodological literature on technologies for the development of the lexical and grammatical aspects of speech in children with severe speech defects.